Customer satisfaction towards service quality in banking industry: a case study at the main branch of Maybank in Malacca / Nur Fatin Atiqah Mohamad Nasir and Norul Khairunnisa Razali - Mohamad Nasir, Nur Fatin Atiqah; Razali, Norul Khairunnisa (Faculty of Administrative Science and Policy Studies, 2013)
In modern economics, service sector plays significant role side by side manufacturing and other sectors. Banking sector performs its activities economically and socially in a country especially in the developing country such as Malaysia. In the banking industry, a customer can be defined as a user or potential user of banking services. A customer would include an account holder, or carrying out casual business transactions with a bank A key element of customer satisfaction in the banking sector is the nature of the relationship between the customers and the banking service providers. The efficiency of a banking sector depends upon how best it can deliver services to its target customers. In order to survive in the competitive environment and provide continual customer satisfaction, the banking service providers are required to frequently increase the quality if services.However, banks may not be able to provide superior services to the customers unless customer expectations are known.